Pemberdayaan UMKM Simping & Gapit Sri Logay Melalui Analisis SWOT dan Metode USG: Penelitian - Juliani Lisma Sari (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The Community Service Program integrated into the Community Practice Course–Field Work Practice (KPB-PKL) was conducted at UMKM Simping & Gapit Sri Logay in Purwakarta. This activity aims to broaden students’ knowledge and enhance their competencies, as well as contribute to UMKM development through SWOT analysis and the determination of problem priorities using the USG (Urgency, Seriousness, Growth) method. The implementation involved direct observation, interviews, and documentation collection. The findings indicate that the UMKM possesses several strengths, such as consistent product quality and complete business legality; however, it still faces challenges in the form of limited digital marketing efforts and inadequate financial recording systems. Based on the results of the USG analysis, the problem with the highest level of urgency is the lack of digital marketing. The recommended strategies include digital marketing training and packaging innovation improvement. This program contributes to enhancing business owners’ understanding and supports the formulation of more directed business development strategies.